Use of Antimicrobial-Coated Catheters in Preventing Catheter-Associated Urinary Tract Infections and Bacteriuria: A Meta-Analysis for Clinicians. Issue 6 (18th November 2021) - Vopni, Rachel; Voice, Alesia; de Riese, Cornelia S.; Garza, John; de Riese, Werner T.
Abstract: Introduction: Catheter-associated urinary tract infections comprise a significant burden to the health care system and are of major concern for indwelling catheter use. Catheter coatings have been studied for their potential to reduce risk of infection. The purpose of this meta-analysis is to determine the efficacy of coated catheters across clinical studies in preventing these common nosocomial infections. Methods: Searches were conducted on PubMed Central® and ScienceDirect using the terms "catheter, " "urinary tract infection" and "coated" or "antimicrobial." Articles included were prospective randomized clinical studies of coated (experimental) vs uncoated (control) catheters published in English between the years 2000 and 2020. Results from included studies were analyzed using Fisher's exact test and conditional logistic regression. Results: Fifteen studies met the inclusion criteria. Tested urinary catheter coatings include silver, silver salt, nitrofurazone and metal-alloy. Conditional logistic regression (p < 0.001) shows statistically significant negative association between coated catheter use and the incidence of catheter-associated urinary tract infections. The odds ratio of 0.80 and 95% confidence interval (0.74, 0.88) support protective effect of catheter coatings. Conclusions: Meta-analysis demonstrates a negative association of coated catheter and incidence of catheter-associated urinary tract infections, supporting that antimicrobial catheter coatings decreases incidence of infection across studies. Further clinical research is recommended to determine the potential for catheter coating adoption in clinical practice to reduce catheter-associated urinary tract infection risk and incidence.